Identification of a Glypican-3 Binding Peptide From a Phage-Displayed Peptide Library for PET Imaging of Hepatocellular Carcinoma - Yan, Jiayao; Yu, Xiaoxiao; Chen, Xiaotong; Liu, Fangcen; Chen, Fangjun; Ding, Naiqing; Yu, Lixia; Meng, Fanyan; Shen, Jie; Wei, Jia; Liu, Baorui (Frontiers in Oncology, 2021)
Tumor-targeting peptides functioned as molecular probes are essential for multi-modality imaging and molecular-targeting therapy in caner theronostics. Here, we performed a phage-displayed bio-panning to identify a specific binding peptide targeting Glypican-3 (GPC-3), a promising biomarker in hepatocellular carcinoma (HCC). After screening in the cyclic peptide library, a candidate peptide named F3, was isolated and showed specific binding to HCC cell lines. In a bio-distribution study, higher accumulation of F3 peptide was observed in HepG-2 tumors compared to PC-3 tumors in xenograft models. After labeling with radioactive 68Ga, the F3 peptide tracer enabled the specific detection of tumors in HCC tumor models with PET imaging. More importantly, the expression of GPC-3 in human tissue samples may be distinguished by an F3 fluorescent peptide probe indicating its potential for clinical application. This cyclic peptide targeting GPC-3 has been validated, and may be an alternative to serve as an imaging probe or a targeting domain in the drug conjugate.